ANALISIS PERAN KANTOR PERTANAHAN KABUPATEN KULON PROGO DALAM SENGKETA PERTANAHAN DI DESA KARANGWUNI - Aini, Auladina Nur; ., Kushandajani; Manar, Dzunuwanus Ghulam (Journal of Politic and Government Studies, 2016)
Pakualam Ground is communal land that is regulated under Law No. 3 Year 1950 on the Establishment of the Special Region of Yogyakarta that land sector into domestic affairs and obligations of the Government of Yogyakarta Special Region (DIY). So that Law No. 5, 1960 (Basic Agrarian Law) does not apply fully in Yogyakarta. As owner of the land Pakualaman Ground, Paku Alam has not been recognized as a legal entity in Indonesian positive law so it is entitled to a certificate as evidence of ownership of land. This resulted the certainty about the location and boundaries of the land becomes less clear. So frequently lead to land dispute, such as mutual claims of land ownership Paku Alam Ground.This study aims to identify the factors causing land dispute and the role of Kulon Progo District Land Office to resolve land dispute in Karangwun village. The research method used is qualitative. Analysis techniques using analysis interactive models of Miles and Huberman with analysis in the form of data collection, data presentation, data reduction and then drawing conclusions / verificationBased on research that has been done, it is known that factors causing land dispute in Karangwuni village is the disorganized land administration in the past are boundary Paku Alam Ground. The second factor is the conflict of data related to different perceptions about the land boundary. Kulon Progo District Land Office plays a role in conducting an inventory of land and issuance of certificates. It can be concluded that the Kulon Progo District Land Office role in the settlement of land dispute in the village Karangwuni.Keywords : Land disputes, Paku Alam Ground, Role